Travel, space, architecture - Traganou, Jilly, 1966-; Mitrašinović, Miodrag, 1965- (Design and the built environment series., 2009)
"In alligning architectural thinking with current critical theory debates, this book argues forcefully that by dissociating culture from place and identity, and detaching the idea of architecture from both, we can reframe our understanding of spatial and architectural practices."--Page 4 of cover.